30.1k views
2 votes
25-(3x+5)=2(x+8)+x step by step

User Mujahid
by
5.9k points

1 Answer

3 votes

Steps:

The initial expression is:


25-(3x+5)=2(x+8)+x

Applying the distributive property:


\begin{gathered} 25-3x-5=2\cdot x+2\cdot8+x \\ 25-3x-5=2x+16+x \end{gathered}

Adding like terms:


20-3x=3x+16

Subtracting 16 on both sides of the equation:


\begin{gathered} 20-3x-16=3x+16-16 \\ 4-3x=3x \end{gathered}

Adding 3x on both sides:


\begin{gathered} 4-3x+3x=3x+3x \\ 4=6x \end{gathered}

Dividing by 6:


\begin{gathered} (4)/(6)=(6x)/(6) \\ (2)/(3)=x \end{gathered}

Answer: x = 2/3

User Saarrrr
by
4.7k points